Pengaruh Kombinasi Slow Deep Breathing dan Cryotherapy terhadap Nyeri Akibat Tusukan Fistula Arteriovenosa Pada Pasien Hemodialisis: Case Report - Afif Tiara Khusna; Ida Nurjayanti; Agus Rismanto (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2024)
A problem often experienced by hemodialysis patients is pain when puncturing an arteriovenous fistula. Hemodialysis patients with AVFs experience an average of ten AVF punctures every month, lasting their entire lives. Persistent pain can negatively affect a patient's health, functional ability, and quality of life. This research uses a Case Report approach with nursing care. The intervention was carried out on a scale with structured data collection using the Numeric Scale Rating. The aim of this study was to examine the effect of a combination of slow deep breathing and cryotherapy on arteriovenous fistula puncture. This case study carried out data collection through interviews, intervention, evaluation and documentation. The results of this case study showed that the combination of Slow Deep Breathing and Cryotherapy was effective in reducing pain due to AV fistula puncture in hemodialysis patients. Before the intervention was carried out, the pain scale for both respondents was 6 (moderate pain), but after the intervention with Slow Deep Breathing and Cryotherapy for 4 sessions for 15 minutes, the pain scale decreased to 2 (mild pain).